2005
DOI: 10.1002/mc.20175
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase isozymes are expressed in human myeloma cells but not involved in anti‐proliferative effect of cyclooxygenase inhibitors

Abstract: Considering possible tumorigenic activity of cyclooxygenase (COX) isozymes in myeloma, we examined expression levels of COX-1 and -2 in seven human myeloma cell lines (ARH-77, IM-9, RPMI-8226, HPC, HS-Sultan, TSPC-1, and U-266). As analyzed by reverse transcriptase-polymerase chain reaction (RT-PCR), all the cell lines constitutively expressed COX-1, while COX-2 levels markedly varied among different cell lines. Induction of COX-2 by phorbol ester was observed in RPMI-8226 and HPC cells. In contrast, COX-2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
(62 reference statements)
0
10
1
Order By: Relevance
“…However, only the COX-2 inhibitor, NS398, and not the COX-1 inhibitor, SC560, suppressed proliferation of two MM cell lines, indicating that COX-2 suppression plays an inhibitive role in MM cell proliferation. These findings were inconsistent with a previous report that both COX-1 and COX-2 inhibitors suppress proliferation of ARH-77 cells, but the supplementary concentrations in that study are higher (100 M) than those in our study (30 M) or the general dosage (10 M) (12). In addition, TxB 2 production was also decreased by COX-2 inhibitor, but not COX-1 inhibitor, similar to their effects on MM cell proliferation, suggesting that NS398 inhibits TxB 2 synthesis to delay cell proliferation, which is supported by previous findings in lung adenocarcinoma cells (10).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, only the COX-2 inhibitor, NS398, and not the COX-1 inhibitor, SC560, suppressed proliferation of two MM cell lines, indicating that COX-2 suppression plays an inhibitive role in MM cell proliferation. These findings were inconsistent with a previous report that both COX-1 and COX-2 inhibitors suppress proliferation of ARH-77 cells, but the supplementary concentrations in that study are higher (100 M) than those in our study (30 M) or the general dosage (10 M) (12). In addition, TxB 2 production was also decreased by COX-2 inhibitor, but not COX-1 inhibitor, similar to their effects on MM cell proliferation, suggesting that NS398 inhibits TxB 2 synthesis to delay cell proliferation, which is supported by previous findings in lung adenocarcinoma cells (10).…”
Section: Discussioncontrasting
confidence: 99%
“…Li et al (30) have shown that COX-2 siRNA transfection can suppress COX-2 protein expression in RPMI-8226 cells, which leads to growth inhibition and apoptosis independent of Bcl-2. Another study (12) has shown that seven human myeloma cell lines constitutively express COX-1 mRNA, whereas COX-2 levels vary markedly among cell lines and are not detectable in U-266 and RPMI-8226 cells. In the present study, we examined protein level expression of both COX-1 and COX-2 in RPMI-8226 and U-266 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations suggest that Cox-2 selective inhibitors might boost the efficacy of chemotherapeutic treatments already in clinical use. In contrast, investigators performing a similar study showed that ARH-77 and IM-9 MM cell lines expressed Cox-2 mRNA, while RPMI8226, U266 were negative for Cox-2 [45]. ARH-77 cells contained enzymatically active Cox-2 and produced PGE 2 and PGF 2α , whose production was inhibited by Cox-2 selective inhibitors.…”
Section: Multiple Myelomamentioning
confidence: 92%